Photoperiodic Flowering Response of Essential Oil, Grain, and Fiber Hemp (Cannabis sativa L.) Cultivars - Zhang, Mengzi; Anderson, Steven L.; Brym, Zachary T.; Pearson, Brian J. (Frontiers in Plant Science, 2021)
Cultivation of hemp (Cannabis sativa L.) in tropical and subtropical regions can be challenging if flowering behavior of a given cultivar is unknown, poorly understood, or not accurately selected for the photoperiod. Identifying cultivars adapted to local environmental conditions is key to optimizing hemp vegetative and flowering performance. We investigated the effects of varying light cycles in regulating extension growth and flowering response of 15 essential oil and 12 fiber/grain hemp cultivars both in indoors and outdoors. Plants were subjected to eleven photoperiods in the controlled rooms ranging from 12 h to 18 h, and natural day length in the field. The critical photoperiod threshold was identified for seven essential oil cultivars and two fiber/grain cultivars. ‘Cherry Wine-CC’, ‘PUMA-3’, and ‘PUMA-4’ had the shortest critical day length between 13 h 45 min and 14 h. The flowering of essential oil cultivars was generally delayed by 1 to 2 d when photoperiod exceeded 13 h compared to 12 h, and flowering was further delayed by 7 to 8 d when photoperiod exceed 14 h. In fiber/grain cultivars, flowering was generally delayed by 1 to 3 d when day length exceeded 14 h. Flowering for most essential oil cultivars was delayed by 5 to 13 d under 14 h photoperiod compared to 13 h 45 min, suggesting a photoperiod difference as little as 15 min can significantly influence the floral initiation of some essential oil cultivars. Cultivars represented by the same name but acquired from different sources can perform differently under the same environmental conditions, suggesting genetic variation among cultivars with the same name. Average days to flower of fiber/grain cultivars was correlated with reported cultivar origin with faster flowering occurring among northern cultivars when compared to southern cultivars. Plant height generally increased as the day length increased in essential oil cultivars but was not affected in fiber/grain cultivars. In addition, civil twilight of approximately 2 µmol·m-2·s-1 was discovered to be biologically effective in regulating hemp flowering. Collectively, we conclude that most of the essential oil cultivars and some southern fiber/grain cultivars tested express suitable photoperiods for tropical and sub-tropical region cultivation.